Peranan Peramalan Penjualan Terhadap Bahan Baku: Studi Kasus Least Square PD Sinar Rejeki Ban Di Kabupaten Pandeglang - Indra Laksana Noerwan; Andri Susilo; Ariri Permana (E-Journal Studia Manajemen, 2013)
The aim of this study was to determine the method of quantitative sales forecasting for raw materials. Population in this study are sales data PD Sinar Rejeki Ban in Pandeglang Banten from July 2011 to September 2011. This study using purposive sampling and data collection by observation. Data were analyzed using the least squares method. The study found that there are effects sales forecasting on raw materials.